The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/1043659619859059
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Prevention and Management of Coronary Heart Disease Among Chinese Immigrants and Their Family Carers: A Socioecological Approach

Abstract: Introduction: Health disparities among immigrants exist across socioecological domains. While Chinese immigrants face increased risk for coronary heart disease (CHD) after migration, the reasons are not well understood. Method: This descriptive qualitative study collected 18 semistructured interviews with Chinese immigrants with CHD and family carers from two Australian hospitals. Analysis was guided by the social–ecological model. Results: Poor knowledge and limited English proficiency increased CHD risk and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 39 publications
(52 reference statements)
1
49
0
Order By: Relevance
“…In high-income countries such as Canada and the USA, immigration status can also impact food purchases as immigrants usually incorporate unhealthy and fast foods into their traditional diet (63) . In this context, studies have shown that culture creates challenges to immigrant adherence to dietary recommendations in CR programmes (64,65) . The main reasons for this fact include limited access to familiar foods or ingredients, such as types of vegetables or spices, uncertainty or unfamiliarity with new foods and cultural preparation practices, and digestion problems related to the consumption of unfamiliar products (66)(67)(68) .…”
Section: Discussionmentioning
confidence: 99%
“…In high-income countries such as Canada and the USA, immigration status can also impact food purchases as immigrants usually incorporate unhealthy and fast foods into their traditional diet (63) . In this context, studies have shown that culture creates challenges to immigrant adherence to dietary recommendations in CR programmes (64,65) . The main reasons for this fact include limited access to familiar foods or ingredients, such as types of vegetables or spices, uncertainty or unfamiliarity with new foods and cultural preparation practices, and digestion problems related to the consumption of unfamiliar products (66)(67)(68) .…”
Section: Discussionmentioning
confidence: 99%
“…H. Jang, 2016; Y. Jang et al, 2020; Jin et al, 2020). Hence, the current findings acknowledge the importance for future immigrant-related research to consider the percentage of immigrants residing in the community along with using culturally tailored community resources to improve health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies reported that limited information on analgesic use was associated with inappropriate use of analgesics and overdose of acetaminophen (Saengcharoen et al, 2016). A recent study showed that Asian Americans reported the lowest health literacy levels among racial minorities (Bakker et al, 2017), and low health literacy has been found to contribute to health disparities among immigrants (Jin et al, 2020; H. Y. Lee, Choi, et al, 2015; Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This combination of inductive and deductive analysis has been used in past descriptive qualitative research to enhance theoretical rigour. 25…”
Section: Discussionmentioning
confidence: 99%